Hearing thresholds assessment in diabetic patients at Hospital University Sains Malaysia, Kubang Kerian - Sharma, Hari Shankar; Bebakar, Wan Mohamad Wan (1999)
Clinical records of 542 patients from the diabetic clinic at Hospital Universiti Sains Malaysia were screened for the various factors which are known to cause hearing impairment. There were 28 patients included in the present study and their written consent was taken to participate in the study. Pure tone hearing thresholds for air and bone conduction was done at the ENT clinic and the results were compared with 19 non-diabetic healthy controls using the same screening criteria which was used for the diabetic patients. The diabetic patients were found to have increased hearing thresholds at high frequency (8000Hz) when compared to controls. This hearing loss was found to be more in patients with diabetes mellitus of more than 7 years as compered to the patients having diabetes mellitus of the less than 7 years. The poor controls of diabetes was not found to have positive correlation to this hearing loss. The patients with diabetic retinopathy had significant hearing loss when compared with patients having no diabetic retinopathy. Our results shows that diabetes mellitus causes hearing loss which is similar to the hearing loss seen in the old age. It seems the diabetic patients in our study has early age changes.